Smart Cities Partnership-Innovation for e-services. - Brauckmüller, Jana; Khodabakhsh, Peyman (Steiner, 2017)
This project brought together local authorities and academic partners from 13 cities in the North Sea Region to share ideas and pilot initiatives to make their cities smart. Planners and decision makers from different European countries develop and discuss individual ways to implementing smart cities.
Keywords: Stadtplanung; Gemeinde; Wissenschaft; Kooperation; Technische Infrastruktur; Informationstechnologie; Kommunikationstechnologie; Telekommunikation; Innovation; Planungsgrundlage; Transparenz; Datenerfassung; Smart City; EU-Projekt; Interreg; Wissenstransfer; Stadtsystem; Stadtmanagement; Steuerung; Beschleunigung; Technische Entwicklung; Digitalisierung; Vernetzung; Smartphone; Internationale Zusammenarbeit